18F-fluorodeoxyglucose positron emission tomography to indicate conversion surgery in patients with initially unresectable locally advanced pancreatic cancer. (26th March 2018) - Okano, Keiichi; Suto, Hironobu; Oshima, Minoru; Ando, Yasuhisa; Nagao, Mina; Kamada, Hideki; Kobara, Hideki; Masaki, Tsutomu; Okuyama, Hiroyuki; Okita, Yoshihiro; Tsuji, Akihito; Suzuki, Yasuyuki
Abstract : FDG-PET could be a potential indicator of conversion surgery in patients with primary UR-LA PDAC and may help in selecting optimal patients for complete surgical resection. Abstract: Objective: Advances in chemotherapy and chemoradiotherapy have enabled conversion of initially unresectable locally advanced (UR-LA) pancreatic adenocarcinoma (PDAC) to a resectable disease. However, definitive criteria for conversion surgery have not been established. We evaluated the potential of 18 F-fluorodeoxyglucose positron emission tomography (FDG-PET) to indicate conversion surgery in patients with primary UR-LA PDAC. Methods: Twenty consecutive patients with UR-LA PDAC underwent chemoradiation or chemotherapy followed by assessment with FDG-PET. We defined PET responders (standardized uptake value <3.0) with marked reduction (>80%) of carbohydrate antigen 19-9 as potential candidates for conversion surgery. Outcomes were compared with those of the patients with resectable (R; n = 94) and borderline resectable (BR; n = 37) PDAC. Results: Eight of the 20 patients (40%) were considered PET responders with marked reduction of CA19-9 and received conversion surgery (UR-LAR) 3–9 months (median, 5 months) after the initiation of therapy. Complete resection (R0) was achieved in 7 of 8 patients (87.5%) with UR-LAR. There was no significant difference in R0 rates, morbidity, or mortality among the UR-LAR, R and BR groups. The overall survival (OS) curve was better in the UR-LAR group than in the group that did not receive surgery. There was no significant difference in OS between the UR-LAR and the R or BR groups. Conclusions: FDG-PET could be a potential indicator for conversion surgery in patients with primary UR-LA PDAC and may help in selecting patients who qualify for complete surgical resection and have a promising prognosis.